Persistent genital arousal disorder it’s etiology, treatment guideline and management strategy - Singh, Preksha T.; Singhvi, Shreyans D. (International Journal of Research in Medical Sciences, 2020)
Persistent genital arousal disorder is a recently recognized disorder. Its first case was reported in 2001, since then many cases have been diagnosed and treated with various methods, yet no FDA approved treatment guidelines have been proposed. Although it is a cause of not only sexual, but also psychological impairment to the patients of the disorder, Persistent genital arousal disorder is not well recognized currently due to the social stigma attached to it This study is important for the physicians treating a case of PGAD, as it has all the published data about the disorder. The review of literature was done by using all the research articles and case reports of PGAD using keywords like ‘persistent’, ‘genital’, ‘arousal’, ‘disorder’ on platforms like google scholar and pubmed. Various research articles and case reports were reviewed and grouped into different levels of intervention; at the female genital system, at the spinal cord and the brain. This study has evaluated all the possible etiologies and suggested the possible treatments and management strategies for the disorder. This study has thrown striking limelight on all the potential causes leading to PGAD, its potential line of treatment, and the management strategy. This study is based on the case reports found till date, but there is still a paucity in data, the number of reported cases is less due to a possible social stigma associated with the disease. The present investigation demands extensive research in the topic as this is a cause of social concern leading to psychological, emotional and nervous breakdown.